(untitled) (Journal of the College of Education for Women, 2019)
Five mixed primary schools from the district of Tikrit/ Salah al- din provincewith a total of 100 male and female pupils and two ages(8-9 and 10-11 years),were selected randomly to study the relationship between the breakfast meal andthe academic level, the socioeconomic situation, and the number of familymembers. The study showed a positive linear correlation between the morningmeal, and academic level of students for both two covered ages, also showed aclear impact between the development of family’s socioeconomic situation andtheir nutrition level. There were an increase in the percentage of pupils aged 8-9years with a poor nutrition when they were belonged to a poor or mediumsocioeconomic families, with the absence of students with poor nutrition at theimprovement family level to very good. The medium level of nutrition indicates ahigher percentage when the students belongs to a good economic situation, whilethe level good and very good nutrition gives an increase in the percentage ofstudents; with the improvement at the socioeconomic level of the family with adifferent rates of increasing, noting the absence of students with good andvery good nutrition in the case of inferior status of the family. Same relationship forpupils aged 10-11 were shown. Also there were an effect of the number of familymembers to which these students were belonged on the level of nutrition, therewere a decrease in the level of nutrition for these students commensurate with theincrease in family members for both two covered age. From this we can concludethat there were an opposite effect for both of the socioeconomic situation, and thenumber of family members on the academic level of the students for both twocovered ages.